Effect of different financial competing interest statements on readers' perceptions of clinical educational articles: study protocol for a randomised controlled trial. Issue 6 (10th June 2016) - Schroter, Sara; Pakpoor, Julia; Morris, Julie; Chew, Mabel; Godlee, Fiona
Abstract : Introduction: Financial ties with industry are varied and common among academics, doctors and institutions. Clinical educational articles are intended to guide patient care and convey authors' own interpretation of selected data. Author biases in educational articles tend to be less visible to readers compared to those in research papers. Little is known about which types of competing interest statements affect readers' interpretation of the credibility of these articles. This study aims to investigate how different competing interest statements in educational articles affect clinical readers' perceptions of the articles. Methods and analysis: 2040 doctors who are members of the British Medical Association (BMA) and receive a copy of the British Medical Journal (The BMJ) each week will be randomly selected and invited by an email to participate in the study. They will be randomised to receive 1 of 2 Clinical Reviews, each with 1 of 4 possible competing interest statements. Versions of each review will be identical except for permutations of the competing interest statement. Study participants will be asked to read their article and complete an online questionnaire. The questionnaire will ask participants to rate their confidence in the conclusions drawn in the article, the importance of the article, their level of interest in the article and their likeliness to change their practice from the article. Factorial analyses of variance and analyses of covariance will be carried out to assess the impact of the type of competing interest statement and Clinical Review on level of confidence, importance, interest and likeliness to change practice. Ethics and dissemination: The study protocol, questionnaire and letter of invitation to participants have been reviewed by members of The BMJ's Ethics Committee for ethical concerns. The trial results will be disseminated to participants and published in a peer-reviewed journal. Trial registration number: NCT02548312; Pre-results.